2021
DOI: 10.1098/rsos.201933
|View full text |Cite
|
Sign up to set email alerts
|

Black kites of different age and sex show similar avoidance responses to wind turbines during migration

Abstract: Populations of soaring birds are often impacted by wind-power generation. Sex and age bias in turbine collisions can exacerbate these impacts through demographic changes that can lead to population decline or collapse. While several studies have reported sex and age differences in the number of soaring birds killed by turbines, it remains unclear if they result from different abundances or group-specific turbine avoidance behaviours, the latter having severer consequences. We investigated sex and age effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…S1 ), likely reflecting the most common turning angles of birds actively avoiding wind turbines when previously in a collision trajectory. Previous analyses with subsets of this data showed that birds exhibited inflated densities around 700–800 m from the wind turbines 10 , 13 , probably corresponding to trajectory changes with similar turning angles intended to avoid approaching wind turbines further. This pattern was also observed in other migrating raptors tracked by radar (see Fig.…”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…S1 ), likely reflecting the most common turning angles of birds actively avoiding wind turbines when previously in a collision trajectory. Previous analyses with subsets of this data showed that birds exhibited inflated densities around 700–800 m from the wind turbines 10 , 13 , probably corresponding to trajectory changes with similar turning angles intended to avoid approaching wind turbines further. This pattern was also observed in other migrating raptors tracked by radar (see Fig.…”
Section: Methodsmentioning
confidence: 83%
“…1 ). Further details on field procedures and tracking equipment can be found in earlier publications with subsets of these data 10 , 13 , 19 .
Figure 1 Left panel shows the spatial distribution of bird and turbine locations in the study area between Cadiz and Tarifa (southern Spain).
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the data from 68 of the 71 studies to assess the current knowledge on bird displacement, with a total of 286 trials. We excluded three studies from this analysis [24][25][26], whose information was duplicated, at least partially, in other works. We stress that, as the considered studies implemented quite variable methodological approaches (see previous section), comparisons across studies and taxa should be conducted with caution.…”
Section: Current Knowledge On Bird Displacement By Wind Turbinesmentioning
confidence: 99%